Ketersediaan Kelembagaan dalam Pengembangan Usahatani Rumput Laut (Eucheuma spinosum) di Desa Kawite Wite Kecamatan Kabawo Kabupaten Muna - Ramadan, Ramadan; Alwi, La Ode; Yusria, Wa Ode (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This research aims to know and identify the institutional conditions are available and knowing the strategies of the community in case of institutional infrastructure limitations in the development of farming seaweed. The type of the data being used is the primary data and secondary data. Data analysis using the method of analyses tabulations and descriptive and analysis Quantitative Strategic Planning Matrix (QSPM). The results showed that (1) the availability of the institutional in the development of farming seaweed consisting of capital providers, information providers, and the institutions of providing inputs. The institution that provides capital in the development of seaweed farming in Kawite Wite Villagenamely collecting merchants. Institutions that provide information namely collecting merchants and extension officers, and institutional agencies providing input namely collecting merchants. The priority of the strategy can be done by farmers who do the farming of seaweed in Kawite Wite Village, Kabawo Subdistrict Muna Regency is a strategy 1 (one), namely the Human Resource training and development strategy for farmers worth 12.096. While on strategy 2 (two) as a strategy to optimize the results of production worth 11.311 and strategy 3 (three), namely expanding network marketing strategy valued at 10.685.